Surfactin: a novel Aphis gossypii killing surfactin produced by Bacillus australimaris TRM82479 of Taklamakan Desert origin - Wang, Yelin; Sun, Zhibin; Wang, Shiyu; Wen, Feng; Xia, ZhanFeng (Frontiers in Microbiology, 2025)
IntroductionThe cotton aphid Aphis gossypii poses a global, serious threat to cotton yield and quality. Although chemical pesticides are effective, pollution and resistance are increasingly prominent, making development of new biopesticides a priority in the context of green agricultural development.MethodsGiven that reports on the activity of surfactins against A. gossypii are limited, here, 107 Bacillus strains isolated from the extreme environment of the Chinese Taklamakan Desert were screened for insecticidal activity against A. gossypii using the leaf-dip method. Active strains were characterized by morphological observation, 16S rRNA gene sequencing, and phylogenetic analysis. Secondary metabolite synthesis genes were identified by whole-genome sequencing and antiSMASH analysis.ResultsB. australimaris strain TRM82479 showed 75.00% 48-h mortality against A. gossypii. An antiSMASH analysis showed that this strain contains several gene clusters related to the synthesis of nonribosomal peptide (NRP) fengycin and lichenysin lipopeptide analogs. Cluster 1 has the highest similarity of 52% with the fengycin synthesis gene cluster, and Cluster 8 has the highest similarity of 92% with the lichenysin synthesis gene cluster. It is inferred that B. australimaris strain can produce lipopeptide analogs distinct from fengycin and lichenysin, so we isolated and identified its NRPs. The results showed that surfactin is the main insecticidal substance, with an LC50 of 0.857 mg/mL and an LC95 of 4.350 mg/mL against cotton aphids in aqueous solution. The results of the zebrafish acute toxicity experiment showed that surfactins are low-toxic to fish, indicating good biological safety.DiscussionThis study not only provides new strain resources for cotton aphid control but also demonstrates the potential of surfactins as biopesticides, laying a foundation for their future agricultural application.